Strain Engineering in Electrocatalysts: Fundamentals, Progress, and Perspectives. Issue 5 (22nd December 2021) - Yang, Xiaobo; Wang, Yingyong; Tong, Xili; Yang, Nianjun
Abstract: Strain engineering of nanomaterials, namely, designing, tuning, or controlling surface strains of nanomaterials is an effective strategy to achieve outstanding performance in different nanomaterials for their various applications. This article summarizes recent progress and achievements in the development of strain‐rich electrocatalysts (SREs) and their applications in the field of electrochemical energy conversion technologies. It starts from the definition of lattice strains, followed by the classification of lattice strains where the mechanisms of strain formation and the reported methods to regulate related strains are elaborated. The SRE characterization techniques are overviewed, focusing deeply on the clarification of the strain‐property relationship of these SREs. Their applications for different electrocatalytic reactions are further highlighted, including the hydrogen evolution reaction, oxygen reduction reaction, oxygen evolution reaction, alcohol oxidation reaction, electrochemical carbon dioxide reduction reaction, and nitrogen reduction reaction. Related reaction mechanisms of the SREs are interpreted after taking catalytic performance, as well as the relationship between the SRE properties and their strains into account. The challenges and future opportunities to regulate SREs are finally outlined and discussed together with their potential applications in different fields. Abstract : This review provides a comprehensive summary on the fundamentals, characterization, and applications of strain‐rich electrocatalysts (SREs). The mechanisms of strain formation in different electrocatalysts are highlighted together with several exemplar electrocatalytic reactions such as, water splitting, alcohol oxidation, CO2 reduction, and nitrogen fixation. The prospects of SREs are also discussed and outlined.